Assessment of nucleic acid content, amino acid profile, carcass, and meat quality of Thai native chicken - Niraporn Chaiwang; Kulisara Marupanthorn; Nuttawut Krutthai; Watcharapong Wattanakul; Sanchai Jaturasitha; Chaiwat Arjin; Korawan Sringarm; Phatthawin Setthaya (Poultry Science, 2023)
ABSTRACT: Functional foods are innovative products that hold health-enhancing potential. They are contributing to changing trends in both consumer behavior and the market. This study was conducted to investigate the effects of breed on the nucleic acid content, amino acid profile, carcass, and meat quality of different breeds of chickens. The outcomes of which could lead to the production of functional chicken meat. In this experiment, 4 genotypes of chicken, namely commercial broilers (CBR), Thai native chickens (Mae Hong Son; MHS), Thai native chickens (Pradu Hang Dam; PHD), and male layer chickens (MLC), were fed commercial feed and reared under identical conditions. All chickens were slaughtered at the market age, whereas the breasts and thighs were separated from the carcasses to determine chemical composition and meat quality. The results indicated that carcass and meat quality traits were significantly different (P < 0.05) among chicken breeds and meat parts. Notably, commercial breeds (CBR and MLC) were superior in performance and carcass quality when compared with the Thai native chickens (MHS and PHD). CBR had the highest growth performance and carcass quality traits (P < 0.01), whereas MHS exhibited the lowest weight gain (P < 0.05). However, Thai native chickens were lower in fat, cholesterol, triglycerides, purine, and uric acid (P < 0.05) contents than the commercial breeds. Interestingly, MHS contained the lowest purine and malondialdehyde levels when compared with the other breeds (P < 0.01). Moreover, MHS contained the highest amounts of glutamic acid in both the breasts and thighs (P < 0.05). Therefore, the meat of MHS may be classified as a functional chicken meat, as it was found to have a pleasant meaty taste and hold nutritional value, which positively influences consumers’ health.